Improving the use of natural and semi-natural grasslands in Mediterranean ruminant systems: issues, options and perspectives - Jouven M.; Casasús I.; Franca A. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Mediterranean small-ruminant systems (MSRS) have undergone an intensification process triggered by local and global changes. Recent research suggests that such tendency should be reversed. This paper provides insight about how increasing the contribution of grasslands (including natural and semi-natural, improved or temporary grasslands) to the feeding system can improve MSRS’ sustainability. Products from grazing animals are ethically appreciated and display good nutritional quality, specific organoleptic characteristics and possibly a longer shelf-life; they can be traced, and thus differentiated. The large surface area of natural and semi-natural grasslands (including areas with shrubs and trees) gives MSRS a head start in terms of carbon sequestration, which can be increased further by an appropriate grazing and feeding management. Technical options to increase grazed grass in MSRS include: (1) producing locally-adapted seed mixtures for grasslands; (2) increasing the proportion of legumes in grasslands; (3) managing grazing in order to maximize the amount and quality of intake; (4) matching the diversity of natural and semi-natural grasslands to animal requirements and/or providing strategic supplementation; (5) reconsidering the value of trees and the interest of foliage as forage. Digital technologies can help to improve farmers’ working conditions and build the ecological knowledge necessary to implement adaptive management strategies. At a socio-political level, it is important to recognize the peculiarities of silvopastoral systems, value the ecosystem services provided, foster collective management solutions and facilitate interconnection with other activities.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)